A comparison of aesthetic outcome between tissue adhesive and subcuticular suture in thyroidectomy wound closure in a multiracial country: A randomized controlled trial - Teoh, Li Ying; Chong, Shun Siang; Hoh, Siew Yep; Teoh, Mei Shi; Ng, Khoon Leong (Elsevier, 2019)
Objectives: Monofilament sutures, both absorbable and non-absorbable, have been used for wound closure. Tissue adhesive has been used in closure of clean, low tension wounds. However, there have been very few published studies on the aesthetic outcomes in neck surgeries. The aim of this study is to compare the patients' and doctors’ satisfaction scores in the aesthetic outcome between both methods of closure of thyroidectomy wounds using validated scoring systems. Methods: A double-blinded randomised controlled trial comparing the aesthetic outcome between tissue adhesive and conventional suture was conducted among patients undergoing thyroid and parathyroid surgeries. Ninety-six patients were randomised into two treatment groups. Patients' wounds were scored by an independent observer using the SBSES score at 6 weeks postoperatively and observer component of the POSAS score at 3 months. Results: Forty-nine patients were randomised to the tissue adhesive group while forty-seven patients received the conventional method. There was no statistical difference in the aesthetic outcome using the patient's scoring system between both arms, with a median score of 9 (p = 0.25, SD ± 6.5). The observer's satisfaction score using POSAS was also not statistically significant (median score of 14 (p = 0.77, SD ± 6.2)). No significance was found in the observer's median score using the SBSES scoring system either (score 3, p = 0.12, SD ± 1.3). However, there was significant reduction in the duration of closure using glue (4.42 mins vs 6.36 mins, p < 0.05). Conclusion: Tissue adhesive offers a comparable cosmetic result to the absorbable suture in thyroidectomy wound closure. © 2018